2016
DOI: 10.1158/0008-5472.can-16-0353
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxyvitamin D and Risk of Breast Cancer in Women Followed over 20 Years

Abstract: Experimental evidence supports a protective role of 25-hydroxyvitamin D (25(OH)D) in breast carcinogenesis, but epidemiologic evidence is inconsistent. Whether plasma 25(OH)D interacts with breast tumor expression of vitamin D receptor (VDR) and retinoid X receptor-alpha (RXR) has not been investigated. We conducted a nested case-control study in the Nurses’ Health Study, with 1,506 invasive breast cancer cases diagnosed after blood donation in 1989–90, 417 of whom donated a second sample in 2000–02. VDR and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…In a recent study by Eliassen et al, no overall association was found between plasma 25(OH)D levels and risk for breast cancer, although a reduced risk was found for women having higher levels when compared with the those in the lowest quintile in the summer (RR, 0.66; 95% CI, 0.46–0.94; P trend = .01) 57 . More recently, McDonnell et al reported that in women with 25(OH)D levels ≥40 ng/mL, a 67% lower risk of breast cancer was found vs women having serum levels <20 ng/mL (HR, 0.33; 95% CI, 0.12–0.90) 58 .…”
Section: Vitamin Dmentioning
confidence: 87%
See 1 more Smart Citation
“…In a recent study by Eliassen et al, no overall association was found between plasma 25(OH)D levels and risk for breast cancer, although a reduced risk was found for women having higher levels when compared with the those in the lowest quintile in the summer (RR, 0.66; 95% CI, 0.46–0.94; P trend = .01) 57 . More recently, McDonnell et al reported that in women with 25(OH)D levels ≥40 ng/mL, a 67% lower risk of breast cancer was found vs women having serum levels <20 ng/mL (HR, 0.33; 95% CI, 0.12–0.90) 58 .…”
Section: Vitamin Dmentioning
confidence: 87%
“…Worldwide, plants have been used for healing since ancient times 57 . Only recently has the interest in using botanicals for medicine risen in the United States, while in Asia, South America, and Africa, the use of local plants is a primary component of medical treatment.…”
Section: Botanical and Other Supplementsmentioning
confidence: 99%
“…Sulforaphane was found to inhibit proliferation, angiogenesis, and metastasis as well as induce cell cycle arrest and apoptosis in breast cancer cells. In addition, sulforaphane has a marked effect on cell cycle checkpoint controls, cell survival, and/or apoptosis in various other cancer cell lines, though the molecular mechanisms remain poorly understood (Eliassen et al, 2016;Park et al, 2015;Sofi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, confirmation of a link between vitamin D status and breast cancer would raise the possibility that breast cancer development or survival could be modified by strategies to increase serum 25D such as food fortification, use of dietary supplements or prudent increases in sun exposure. While a substantial amount of epidemiological and clinical data support such associations, the cumulative data is inconsistent (4; 912). In many epidemiological studies, the impact of vitamin D status appeared to be limited to sub-groups in a cohort with specific attributes, such as pre- or post- menopausal status, presence of obesity, specific tumor subtype, race/ethnicity or genetic polymorphisms.…”
Section: Introduction To Vitamin D and Breast Cancermentioning
confidence: 99%